The Ashes of 2017 from the Klyuchevskoy and Kambalnyy Volcanoes: A Comparative Mineralogical-Geochemical Analysis - V. I. Silaev; G. A. Karpov; D. V. Kiseleva; L. P. Vergasova; B. A. Makeev; K. V. Tarasov; A. F. Khazov (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2018)
The results of the mineralogical and geochemical study of the ash of the Klyuchevskoy and Kambalnyy volcanoes located in different geological conditions (Klyuchevskoy – Central Kamchatskaya Depression, Kambalnyy - Southeast end Eastern Kamchatka Volcanic Ridge) were obtained in 2017, and allowed making following conclusions. The investigated ashes differ somewhat in chemical composition: the Klyuchevskoy volcano ash is close to andesibasalts, but that from Kambalnyy is close to andesites. According to the normative-mineral composition, they are composed of 65–87% basic plagioclases, 3–22% quartz, 6.5–14% Mg-Fe-Ca silicates (olivine, pyroxene, probably hornblende). In this case, the ashes from the volcano Kambalnyy are characterized by more acidic composition of plagioclase and higher content of quartz.  The accessory minerals found in the ashes are presented by spinels (Ulviya magnetite, magnetite, and chromite), ilmenite, rutile, apatite, zircon, pyrite and native metallic-phase (Al, Cu, Fe). Pelitic (silty) fractions are enriched in quartz, but impoverished in Mg-Fe-Ca silicates. As a small admixture in the ash of the Cumulus volcano, titanite, andradite, kaolinite and gypsum are inherently resurgent. The fact of detecting the filamentous forms of abiogenic condensed organopolymer substance of CNO composition in the investigated ashes is of particular importance. It should be noted that, according to the isotope composition of carbon, these formations are identical to similar threads and particles identified in products of modern volcanism in the Kamchatka-Philippine island arc megabelt. Moreover, the analysis showed the presence in the ashes of the Kliuchevskoy and Kambalnyy volcanoes of the carbon substance, which carbon isotopic composition practically coincides with that in the organic filaments. Ashes contain 50 microelements divided into five groups: alkaline and alkaline earth, hydrolyzed, lanthanides, chalcoceridophiles, semi- and non-metals. The analysis leads to the conclusion that the predominantly plagioclase containing ash from both volcanoes show a 75% geochemical similarity to the deep source matter. According to the shape of the curves of chondritotropic concentrations of lanthanides, the ashes from both volcanoes are close to the basaltic lavas of TTI-50. The insignificance of the Eu anomaly on the most curves and the apparent moderate differentiation of the lanthanides indicate that the fractionation of plagioclases in the primary melts and the significant realization of the fractionation of olivine and pyroxenes are weak. Based on the granulometric and morphological homogeneity of particles and the presence of a significant content of fresh volcanic glass in ash from both volcanoes, it can be assumed that in both cases the ashes were predominantly or largely melt-formed, and primarily associated with deep magmatic chambers. It is supposed that the process of slow rise of magmatic melts with their fractionation and gravitational stratification into the lower Mg-Fe-silicate and upper aluminosilicate parts took place. Last eruption of the aluminosilicate substrate occurred in the ash form. Because of the viscosity and tendency to quick solidification, aluminum silicate magmatic magma plugged the channel thus preventing the eruption of the lava Hawaiian type.